Antioxidant and antimicrobial activities of African nutmeg, pepper and black pepper extract on the quality and shelf-life of chicken nuggets (2015)
A study was conducted using five kilogrammes of manually deboned and comminuted broiler meat to determine the antimicrobial and antioxidant activities of Pepper, Black pepper and African nutmeg extracts on the quality and shelf-life of nuggets stored at 4°C for 12 days in a completely randomised design. The results for the antioxidant effect revealed that lipid oxidation of chicken nuggets were improved by the inclusion of the extracts compared to the control. Total plate count, coliform count and fungal count were significantly (P<0.05) reduced with the addition of African nutmeg extracts during storage. It is concluded that extracts of Pepper, Black pepper and African nutmeg led to retarded oxidative rancidity and microbial growth during refrigerated storage, thereby improving the quality and shelf-life of chicken nuggets.